FORMATION OF THE MUGHAM SINGING SCHOOL IN AZERBAIJAN (LATE 19TH – FIRST HALF OF THE 20TH CENTURIES) - Stsemzal'ska, Aneta (History, Archeology and Ethnography of the Caucasus, 2021)
Mugham plays a significant role in the national culture of modern Azerbaijan. Considering this fact, this article describes the initial period of the formation of the Azerbaijani mugham singing school, that is, the end of the 19th – the first half of the 20th centuries. Based on the results of field research (participant observation, and also interviews in Russian and Azerbaijani languages ​​with representatives of the musical community of the capital of Azerbaijan: performers and listeners of mugham, scientists, publicists, employees of concert halls where mugham performances take place, employees of state institutions who are responsible for development programs culture in the country), and available sources, the author of the article focuses on those socio-historical circumstances and characters that testify to the specifics of the modern singing school of mugham. Therefore, special attention is paid to two soloists and connoisseurs of Azerbaijani music: Jabbar Garyagdioglu and Bulbul. The first of them, although he grew up in the traditional environment of folklore singers, performed mughams in a new, theatrical form on the stages of concert halls. The change in the place and form of mugham performance laid the foundation for the emergence of the main genre of modern national music in Azerbaijan - mugham opera. Bulbul's merit for the formation of the mugham singing school, in turn, is that he developed an original singing technique, the specificity of which is the synthesis of modified norms of vocal performance of classical music of the Western type and folklore art, primarily mugham. Due to technical innovations, the national music of Azerbaijan, colored with a purely folk style, is not only interesting, but also understandable to a foreign listener.
Keywords: khanende; Azerbaijani mugham; mugham opera; Jabbar Garyagdioglu; Uzeyir Hajibeyov; Bulbul; folk music; national culture; Azerbaijan.